The Carpenter 4th Draft - Reid, Victor (My University, 1981)
A literary narrative set in Jerusalem on April 6, 30 A.D., following the arrest and crucifixion of Jesus. The story centers on John Mark, his mother Mary, Roman officer Janus Aurelius, and Jewish leaders. Themes include betrayal, political intrigue, faith, and personal transformation.
356 pgs, Typescript, letter-sized, sepia-toned, in good condition.
Keywords: Historical fiction; Biblical narrative; Jesus of Nazareth; Roman-Jewish politics; Jerusalem; Crucifixion; Passover